Cardiopulmonary fitness in children/adolescents with chronic kidney disease and the impact of exercise training: a systematic review and meta-analysis of observational study and randomized controlled trials - Fan Zhang; Yan Bai; Liuyan Huang; Yifei Zhong (Annals of Medicine)
Background This systematic review and meta-analysis aimed to evaluate differences in cardiopulmonary fitness between healthy controls and children/adolescents with chronic kidney disease (CKD) and the effects of exercise training.Methods PubMed, Embase, Scopus and Web of Science were searched for published studies from reception to 14 June 2023, and updated search on 15 October 2023. The included observational studies reported on cardiorespiratory fitness, included maximal oxygen uptake (VO2max), peak oxygen consumption (VO2peak) and 6-minute walk distance (6MWD), in children/adolescents with CKD and age-matched healthy controls, as well as clinical intervention trials of exercise training on cardiorespiratory fitness in samples of children and/or adolescents up to 19.Results Fifteen observational studies and five clinical trials were included, respectively. The studies found that the mean cardiopulmonary fitness was 1.82 standardized mean differences (SMDs) units (95% confidence interval (95% CI) 1.43–2.20) lower in children/adolescents with CKD than in healthy controls or reference values. Except for pre-dialysis CKD patients, peritoneal dialysis, haemodialysis and kidney transplant recipients had significantly lower cardiorespiratory fitness than healthy controls. The results of a meta-analysis based on a pre-post single-arm trial showed that compared to baseline, exercise training improved the 6MWD by approximately 58.17 m (95% CI 16.27–100.06), with very low evidence.Conclusions This systematic review and meta-analysis of observational studies and clinical trials that included children/adolescents with CKD found that cardiorespiratory fitness is severely reduced in this population and that exercise training may be an effective strategy for improvement. Given the low evidence certainty, additional high-quality trials are necessary.